Hydration‐Facilitated Fine‐Tuning of the AIE Amphiphile Color and Application as Erasable Materials with Hot/Cold Dual Writing Modes. (13th November 2019) - Jin, Hongjun; Li, Hongpeng; Zhu, Zhiyang; Huang, Jianbin; Xiao, Yunlong; Yan, Yun
Abstract: Hydration water greatly impacts the color of inorganic crystals, but it is still unknown whether hydration water can be utilized to systematically manipulate the emission color of organic luminescent groups. Now, metal ions with different hydration ability allow fine‐tuning the emission color of a fluorescent group displaying aggregation induced emission (AIE). Because the hydration water can be removed easily by gentle heating or mechanical grinding and re‐gained by solvent fuming, rewritable materials can be fabricated both in the hot‐writing and cold‐writing modes. This hydration‐facilitated strategy will open up a new vista in fine‐tuning the emission color of AIE molecules based on one synthesis and in the design of smart luminescent devices. Abstract : Leuchtende Wasserfarben : Hydratwasser an Metallionen lässt sich nutzen, um reversibel die Emissionsfarbe organischer lumineszierender Gruppen für die aggregationsinduzierte Emission abzustimmen. Das Hydratwasser kann durch Erhitzen oder mechanisches Mahlen entfernt und durch Bedampfen mit Lösungsmittel zurückgewinnen.